2020
DOI: 10.2991/jase.d.200212.001
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Driven Software Architecture for Fully Autonomous Vehicles

Abstract: The development of self-driving vehicles is often regarded as adding a layer of intelligence on top of classic vehicle platforms. However, the amount of software needed to reach autonomy will exceed the software deployed for operation of normal vehicles. As complexity increases, the demand for proper structure also increases. Moreover, the shift from open, deterministic components to more opaque, probabilistic software components raises new challenges for system designers. In this paper we introduce a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Throughout the paper we use an example from autonomous driving, inspired by [1,10] -the design of a perception system for scene understanding. The system performs three tasks: (1) object detection, which aims to identify the location of all objects in an image, (2) semantic segmentation, which assigns each pixel in an image to a predefined class, and (3) depth estimation, which determines the position of obstacles or the road surface.…”
Section: Modeling Uncertainty During Design (Mudd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the paper we use an example from autonomous driving, inspired by [1,10] -the design of a perception system for scene understanding. The system performs three tasks: (1) object detection, which aims to identify the location of all objects in an image, (2) semantic segmentation, which assigns each pixel in an image to a predefined class, and (3) depth estimation, which determines the position of obstacles or the road surface.…”
Section: Modeling Uncertainty During Design (Mudd)mentioning
confidence: 99%
“…In Fig. 1a and b we present two architecture candidates inspired by [10] and [1]. The relevant functional components are illustrated using circles while the input coming from the camera is depicted with a rectangle.…”
Section: Modeling Uncertainty During Design (Mudd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the impairing influence of drowsiness in manual driving, monitoring the drivers' state and their ability to control the car is one of the main requirements of the third level of automated vehicles [5]. At this automated level, the driver will still be responsible for the car's performance and they should act safely and promptly in case of automated system faults or complex traffic scenarios [6,7]. Notwithstanding research findings [8] showing that learning can interact with fatigue, leading to shorter reaction times, most previous studies demonstrated that drowsiness has a significant influence to increase drivers' reaction time for braking or steering maneuvers in risky situations to prevent accidents [9][10][11].…”
Section: Introduction 1motivationmentioning
confidence: 99%
“…Figure 1. SAE J3106 Levels of Automation in Automotive Vehicles* * (Serban, Poll, & Visser, 2020) ADAS includes a range of features, including adaptive cruise control (ACC), lane keep assist (LKA), forward emergency braking (FEB), etc. While the intention may be to improve passenger and pedestrian safety and enhance the driving experience, the driver must assimilate a lot of new information to properly use the advanced features.…”
Section: Introductionmentioning
confidence: 99%